Configurable Miniaturized 3D Pores for Robust Single‐Nanoparticle Analysis. Issue 2 (13th September 2020) - Liao, Caizhi; Antaw, Fiach; Wuethrich, Alain; Anderson, Will; Trau, Matt
Abstract : Resistive pulse sensing (RPS) has become a pivotal platform for single‐molecule and nanoparticle analysis. Key to RPS is the sensing pore structure, the preparation of which is a subject of active research. While existing schemes produce pores with precise entrance diameters, producing pores with arbitrarily complex, 3D internal structures remains an open problem. Herein, two‐photon polymerization (TPP)‐based nanolithography is introduced for the reliable preparation of customizable RPS pores. For the first time, accurate micro‐ and nanopores with different cone angles are successfully prepared and their performance is studied experimentally and by simulation. Subsequently, accurate 3D pores are studied for selected RPS analysis: cis ‐ and transconical pores for the investigation of the pore's preferential transport capability; symmetrical pores for the electrical tracking of nanoparticle position; and cylindrical pores for the surface charge analysis of chemically distinct nanoparticles of the same size. The TPP nanolithography technique enables tailored 3D pore designs with openings as small as 600 nm in diameter, providing opportunities for new RPS implementations that simultaneously investigate the physical and transport properties of translocating objects. Abstract : Two‐photon polymerization (TPP)‐based nanolithography is introduced for the reliable preparation of customizable resistive pulse sensing (RPS) pores for the first time. These tailored RPS pores are explored as versatile platforms for robust nanoparticle analysis, providing opportunities for the simultaneous investigation of physical/chemical and transporting properties of target objects.